„Kindergarten” keeping-system in farrowing house: effect on reducing the weaning-stress - Győri, Zsolt; Balogh, Péter; Huzsvai, László; Novotniné Dankó, Gabriella (Animal welfare, Ethology and Housing Systems (AWETH), 2015)
The process of weaning is a multifactorial stressor, in which nutritional, social, physical and psychologic stressors are combined. The aim of this study was to examine whether litters’ lettogether system or “kindergarten- system” in the farrowing house before weaning has any effect weight gain and behavior. A total of 302 piglets from 28 litters of Large White x Landrace hybrids were examined. Piglets’ body weight was recorded at birth and every week till the 7th life-week. Continuous video footage was collected in the farrowing house till weaning for behavioral analyses. To monitor and analyze the piglets’ behavior on the day of weaning personal observation was carried out for six hours after housing to rearing crates. There were 12 control litters and 4 experimental groups (4 experimental groups equals 4x4 litters). In the Experimental groups, piglets from 16 sows were socialized pre-weaning (n=179 piglets). Facilitation of socialization of piglets was carried out one week before weaning (20th or 21st day postpartum) by removing 4 adjacent farrowing crate walls. The sows stayed in their cradles, but the piglets could walk, move and get to know each other for a week. The piglets were marked individually on their back; the sows were marked with a colour fitting their piglets. Socialized piglets were monitored to determine the prevalence of cross-suckling and other behavioral events. After weaning the piglets from the same experimental groups were housed to the same rearing crates (4 groups to 4 different crates, n=46; 41; 48; 44 piglets/group). In the Control groups litters from another 12 sows were monitored as control animals (n=123 piglets). The piglets were not mixed in the farrowing house, they stayed in their own farrowing pen till weaning. After weaning the piglets were put to 3 different rearing crates (n= 41 piglets/group). However, there were no significant differences in weight gain between the control and experimental groups, recent work suggested the beneficial effect of “kindergarten” system in the farrowing house in animal welfare aspects.
Keywords: piglet; behavior; weaning; stress